Impacto do barramento de um rio amazônico nos padrões espaciais e temporais da diversidade beta fitoplanctônica. - Zanon, Felipe Morais (2022)
Human activities have caused degradation of aquatic ecosystems and reduced biodiversity. The dams in particular directly impact the spatial and temporal variation of aquatic communities, and especially the phytoplankton community that responds quickly and efficiently to changes in the environment. The impact of a dam in an Amazon river (Jirau Hydroelectric Power Plant) on the spatial and temporal variation of the composition (beta diversity) of phytoplankton was investigated, from October 2009 to July 2017. The hypothesis was tested that the bus modifies beta diversity on a local and regional scale, and alters each location's contribution to beta diversity. The contribution of the sites to the beta diversity was evaluated as a function of the distance from the bus and the environmental heterogeneity. The phytoplankton composition was different between the phases before, fill and after the damming. Biotic homogenization was verified in the tributaries closest to the dam. The more distant sites presented greater contribution to diversity, but were associated with lower values of richness. The dam caused unidirectional changes, locally and regionally, that is, the community moved to a new state over time, and also caused biotic homogenization locally. The impact of the dam was observed only on the tributaries, indicating that run-of-river dams have a greater impact on the tributaries than on the main channel.